2001
DOI: 10.1103/physrevd.64.084017
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal modes of Schwarzschild–anti-de Sitter black holes: Electromagnetic and gravitational perturbations

Abstract: We study the quasi-normal modes (QNM) of electromagnetic and gravitational perturbations of a Schwarzschild black hole in an asymptotically Anti-de Sitter (AdS) spacetime. Some of the electromagnetic modes do not oscillate, they only decay, since they have pure imaginary frequencies. The gravitational modes show peculiar features: the odd and even gravitational perturbations no longer have the same characteristic quasinormal frequencies. There is a special mode for odd perturbations whose behavior differs comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
368
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 332 publications
(401 citation statements)
references
References 33 publications
33
368
0
Order By: Relevance
“…And connection between QNMs and the decay of perturbations in the dual CFT was first suggested in the work of [16] based on the numerical computation of QNMs for AdSSchwarzschild black holes in several dimensions. QNMs of AdS black holes and BTZ black holes are investigated in [17,18,19,20,21,22,23,24,25,26,27] and those of near extremal black branes are found in [28]. Furthermore in [29], it was shown that the frequencies of QNMs for BTZ black holes are in exact agreement with the location of the poles of the retarded correlation function describing the linear response on the CFT side.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…And connection between QNMs and the decay of perturbations in the dual CFT was first suggested in the work of [16] based on the numerical computation of QNMs for AdSSchwarzschild black holes in several dimensions. QNMs of AdS black holes and BTZ black holes are investigated in [17,18,19,20,21,22,23,24,25,26,27] and those of near extremal black branes are found in [28]. Furthermore in [29], it was shown that the frequencies of QNMs for BTZ black holes are in exact agreement with the location of the poles of the retarded correlation function describing the linear response on the CFT side.…”
Section: Introductionsupporting
confidence: 54%
“…In the usual evaluation to QNMs [19,20,21,22,23,24,25,27], their frequencies are characterized by the curvature scale of the black hole space time, i.e. |ωR| ∼ 1.…”
Section: (Q)mentioning
confidence: 99%
“…For example, if the black hole is small, we expect to find in the gravitational radiation spectra a strong peak located at ω 2 = 4n 2 + l(l + 1) , n = 1, 2, ... [5]. Moreover, some major results in perturbation theory and numerical relativity [27,28], studying the collision of two black holes, with masses of the same order of magnitude, allow us to infer that evolving the collision of two black holes in AdS spacetime, should not bring major differences in relation to our results (though it is of course a much more difficult task, even in perturbation theory).…”
Section: Discussionmentioning
confidence: 99%
“…[26], and references therein). Furthermore, the antide Sitter/conformal field theory (AdS/CFT) conjecture [27] has led to an intensive study of black-hole QNM in asymptotically AdS spacetimes in the last few years [28][29][30][31][32][33][34][35][36][37][38][39]. According to the AdS/CFT correspondence, a large static black hole in AdS corresponds to an approximately thermal state in CFT.…”
mentioning
confidence: 99%